The Role of Interpersonal Communication in Handling Tantrum Children in Winduaji Village, Brebes - Juniati, Atika; Turistiati, Ade Tuti; Andhita, Pundra Rengga (Jurnal Komunikasi, 2024)
The presence of smartphone technology has positive and negative impacts on its users, both adults and children. Positive benefits for children: they can gain knowledge and entertainment through smartphones. However, this positive impact can create comfort and addiction, which, if uncontrolled, can have a negative impact. One example is that children have tantrums when their smartphone use is stopped by their parents. This is what happened to children in Winduaji village, Brebes. Interpersonal communication between children and parents plays an important role in handling tantrums in children due to smartphone use. This study aims to determine the strategies or efforts of parents in dealing with tantrum children due to the use of smartphones. This study uses a qualitative descriptive method with observation techniques, in-depth interviews, and document studies, as well as a review of previous research relevant to the research. The results showed that parents’ handling of tantrum children have not been effective based on interpersonal needs theory. It happened because parents lack or even do not involve children in handling tantrums (inclusion), lack of mastery in communication (control), and affection carried out by parents in dealing with child tantrums. Based on operant conditioning theory, parents need to provide positive reinforcement to their children. In addition, parents need to be role models for their children in the use of smartphones that are not excessive.